2022
DOI: 10.1111/ajad.13257
|View full text |Cite
|
Sign up to set email alerts
|

Essential components of physician health program monitoring for substance use disorder: A survey of participants 5 years post successful program completion

Abstract: Background and Objectives: Physician health programs (PHPs) have demonstrated efficacy, but their mechanism of influence is unclear. This study sought to identify essential components of PHP care management for substance use disorder (SUD), and to assess whether positive outcomes are sustained over time.Methods: Physicians with DSM-IV diagnoses of Substance Dependence and/or Substance Abuse who had successfully completed a PHP monitoring agreement at least 5 years before the study (N = 343) were identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A recent study that examined participants over 5 years following treatment completion at a PHP found that two-thirds of physicians rated their treatment as "extremely helpful," with another 17% rating it as "moderately helpful." 13 Additionally, 89% of physicians reported no recurrence during the 5-year monitoring period, while 97% of physicians identified as "in recovery" following treatment. Of note, PHPs provide more concerted and comprehensive care for physicians compared with the members of the general population receiving standard of care and demonstrate better outcomes.…”
Section: Georgetown Medical Reviewmentioning
confidence: 99%
“…A recent study that examined participants over 5 years following treatment completion at a PHP found that two-thirds of physicians rated their treatment as "extremely helpful," with another 17% rating it as "moderately helpful." 13 Additionally, 89% of physicians reported no recurrence during the 5-year monitoring period, while 97% of physicians identified as "in recovery" following treatment. Of note, PHPs provide more concerted and comprehensive care for physicians compared with the members of the general population receiving standard of care and demonstrate better outcomes.…”
Section: Georgetown Medical Reviewmentioning
confidence: 99%
“…This allows PHPs to provide verifying documentation of a participant's compliance with treatment and/or continuing care recommendations. Studies evaluating the long‐term PHP care model for substance use disorders confirm physician recovery rates that are markedly higher than the general population 10,11 . Also, malpractice risk for physicians who successfully complete PHP monitoring is lower than for physicians who have been suspected of impairment but have not yet benefited from PHP intervention 12 …”
Section: Introductionmentioning
confidence: 99%
“…Expenses incurred reflect multiple components of continuing care: independent medical evaluations with providers specializing in assessment of healthcare professionals, intensive treatment, ongoing therapy, and long‐term monitoring including frequent drug testing using expanded panels to detect substances commonly‐used by healthcare professionals. These may vary widely for individual physicians based on the severity of their condition, level of support from their employer/practice partners, and quality of health insurance coverage 11 . Psychosocial sequelae of illness, including financial hardship, combined with unique rehabilitative needs of healthcare professionals, can put the necessary services out of reach, leaving many demoralized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations